Growth of graphene on nickel using a natural carbon source by thermal chemical vapor deposition - Shaharin Fadzli Abd Rahman,; Mohamad Rusop Mahmood,; Abdul Manaf Hashim, (Universiti Kebangsaan Malaysia, 2014)
We report the growth of few-layer graphene (FLG) on a nickel (Ni) substrate using palm oil as a single carbon source by thermal chemical vapor deposition (T-CVD). Using an ample amount of vaporized palm oil resulted in the formation of a thick, amorphous carbon film on the Ni surface. By decreasing the amount of the carbon source supply, thin films consisting of graphite grains and FLG were obtained at growth temperatures of 900 and 1000˚C, confirming the potential of using palm oil as a source for graphene growth. The occasional voids were obtained on the transferred film and these voids were confirmed to be areas where FLGs are formed. These FLGs are likely removed during the transfer process. Further reducing the amount of palm oil suppressed the coverage of graphite grains and increased the void area formation on the transferred films, proving the increase of FLG coverage.